Relationship between children’s skills in school subject learning and athletic ability - Ito, Syuro (Frontiers in Psychology, 2022)
Background and Purpose: Japanese elementary school children are trained in arts and crafts, music, arithmetic, the Japanese language, life environment studies, physical education, and so on. Children must learn through doing as they develop physically, because the range of activities in their daily lives is still narrow. Subject learning is inseparable from daily life. Teachers should plan lessons with an awareness of the physicality of activities. Therefore, this study clarified the relationship between the ability for skillful and quick physical movement and subject learning among Japanese elementary school students. Methods: For the second to fourth grades of elementary school, the measurement results and subject evaluation (skill) were compared at the individual level. Students were divided into a group with high grades in subject learning and one with middle and lower grades, and a t-test was conducted to observe if there was a significant difference in the records of two physical activities: repeated side jump and softball throw. Main Findings: Significant difference was found for repeated side jumps depending on whether the arts and crafts grades were high for all children in grades 2–4. Additionally, there was a significant difference in softball throwing records between the second and third graders, depending on whether the children's performance in arts and crafts was high. Conversely, there was no significant difference between the second to fourth grade children's musical scores and repeated side jump records. There was a negative correlation between sophomore and senior year music performances and the softball throwing record. Thus, the development of children’s dexterity is related to subject learning. Conclusion: Considering that elementary school teachers spend sufficient time with children on a daily basis teaching subjects such as physical education and music, it may be beneficial for them to be aware of dexterity’s importance across multiple subjects. Furthermore, it allows for an approach that engages children in physical activities from early childhood which can help in preparing them for learning a variety of subjects in school.